Bidirectional electron transfer in photosystem I: determination of two distances between P700+ and A1- in spin-correlated radical pairs. - Santabarbara, S; Kuprov, I; Fairclough, W; Purton, S; Hore, P; Heathcote, P; Evans, M (2005)
The spin-correlated radical pair [P(700)(+)A(1)(-)] gives rise to a characteristic "out-of-phase" electron spin-echo signal. The electron spin-echo envelope modulation (ESEEM) of these signals has been studied in thylakoids prepared from the wild-type strain of Chlamydomonas reinhardtii and in two site-directed mutants, in which the methionine residue which acts as the axial ligand to the chlorin electron acceptor A(0) has been substituted with a histidine either on the PsaA (PsaA-M684H) or the PsaB (PsaB-M664H) reaction center subunits. The analysis of the time domain ESEEM provides information about the spin-spin interaction in the [P(700)(+)A(1)(-)] radical pair, and the values of the dipolar (D) and the exchange (J) interaction can be extracted. From the distance dependence of the dipolar coupling term, the distance between the unpaired electron spin density clouds of the primary donor P(700)(+) and the phyllosemiquinone A(1)(-) can be determined. The [P(700)(+)A(1)(-)] ESEEM spectrum obtained in wild-type thylakoids can be reconstructed using a linear combination of the spectra measured in the PsaA and PsaB A(0) mutants, demonstrating that electron transfer resulting in charge separation is occurring on both the PsaA and PsaB branches. The [P(700)(+)A(1B)(-)] distance in the point dipole approximation in the PsaA-M684H mutant is 24.27 +/- 0.02 A, and the [P(700)(+)A(1A)(-)] distance in the PsaB-M664H mutant is 25.43 +/- 0.01 A. An intermediate value of 25.01 +/- 0.02 A is obtained in the wild-type membranes which exhibit both spin-polarized pairs.